(untitled) (Bangladesh Medical Journal, 2019)
Accurate detection of astrocytomas is very difficult. The purpose of the present study was to evaluate the usefulness of MRI in detection of intracranial astrocytoma. This cross-sectional study was conducted at the Department of Radiology and Imaging with the collaboration of Department of Neurosurgery and Department of Pathology at Sir Salimullah Medical College (SSMC & MH), Dhaka from January 2013 to December 2013 for a period of one year. All the clinically suspected and CT scan diagnosed cases of intracranial astrocytoma patients of any age of both sexes were included as study population. All cases having no contraindication for MRI underwent MR examination. MR imaging was obtained with 0.5 Tesla machine (SIEMENS). The postoperative resected tissues were examined histopathological in the respective department. Then the collected reports were compared with findings of MRI. The sample size of the present study was 48 astrocytoma patients. The highest sensitivity was found in grade III astrocytoma (90.5%) followed by grade II (85.7%) grade IV (75.0%) and grade I (60.0%). The highest specificity was found in grade I astrocytoma (97.7%) followed by Grade III (96.3%), grade IV (92.5%) and grade II (91.5%). The highest accuracy was found in both grade I astrocytoma (93.7%) and grade III (93.7%) followed by grade II (92.5%) and grade IV (89.6%). In the conclusion, MRI is an effective tool for the diagnosis of astrocytoma. MRI has a high diagnostic validity for the detection of different grades of astrocytoma. Bangladesh Med J. 2017 May; 46 (2): 48-52